Thin Film Transistors: High‐Performance Flexible Multilayer MoS2 Transistors on Solution‐Based Polyimide Substrates (Adv. Funct. Mater. 15/2016). (April 2016) - Song, Won Geun; Kwon, Hyuk‐Jun; Park, Jozeph; Yeo, Junyeob; Kim, Minjeong; Park, Suntak; Yun, Sungryul; Kyung, Ki‐Uk; Grigoropoulos, Costas P.; Kim, Sunkook; Hong, Young Ki
Abstract : On page 2426, C. P. Grigoropoulos, S. Kim, Y. K. Hong, and co‐workers demonstrate a novel process architecture for flexible electronics. The multilayer molybdenum disulfide thin‐film transistor array fabricated according to this scheme exhibits not only outstanding device performances, but also no apparent degradation under various mechanical stresses. These results could provide important applications in the fabrication of flexible integrated circuitry for various versatile functions.